Staufen1 unwinds the secondary structure and facilitates the translation of fatty acid binding protein 4 mRNA during adipogenesis - Xiaodi Liang; Yi Jiao; Xueli Gong; Hao Gu; Nuerbiye Nuermaimaiti; Xuanyu Meng; Dihui Liu; Yaqun Guan (Adipocyte, 2021)
Adipogenesis is regulated by genetic interactions, in which post-transcriptional regulation plays an important role. Staufen double-stranded RNA binding protein 1 (Staufen1 or STAU1) plays diverse roles in RNA processing and adipogenesis. Previously, we found that the downregulation of STAU1 affects the expression of fatty acid-binding protein 4 (FABP4) at the protein level but not at the mRNA level. This study aimed to determine the mechanism underlying the regulation of FABP4 expression by STAU1, explaining the inconsistency between FABP4 mRNA and protein levels. We used RNA interference, photoactivatable ribonucleoside enhanced cross-linking and immunoprecipitation, and an adeno-associated virus to examine the functions of STAU1 in adipogenesis. Our results indicate that STAU1 binds to the coding sequences of FABP4, thereby regulating the translation of FABP4 mRNA by unwinding the double-stranded structure. Furthermore, STAU1 mediates adipogenesis by regulating the secretion of free fatty acids. However, STAU1 knockdown decreases the fat weight/body weight ratio but does not affect the plasma triglyceride levels. These findings describe the mechanisms involved in STAU1-mediated regulation of FABP4 expression at the translational level during adipogenesis.